Country Pride - Jorquera, Daniela (Base Diseño e Innovación, 2015)
From the moment one enters to Chile by the airport of Santiago. The connection that an alien has with Chilean copper is very direct. In each of the modules where their passport is checked over, when they get off the plane, there is a surface of this material.